Relationship between Compliance with Routine Examination and Quality of Life in Elderly Hypertension - Abigael Rante Toding; Joko Sapto Pramono; Tini (PT FORMOSA CENDEKIA GLOBAL, 2023)
Indonesia has entered an elderly population period with the highest prevalence of hypertension of the entire national population. Hypertension control strategies focus on improving the quality of life for each sufferer so that they can maintain their quality of health independently. Compliance with routine check-ups is a national strategy for controlling cases of hypertension in the elderly. This study aims at the relationship between adherence to routine checks and the quality of life of hypertensive elderly people in the working area of ​​the UPT Puskesmas Tanjung Redeb. From the results of this study, it was found that there was a significant relationship between adherence to routine checks and quality of life for elderly hypertensives in the working area of ​​the UPT Puskesmas Tanjung Redeb (Sig = 0.000; OR = 4.765).